Evaluation of the Predictive Value of Urine Leukocyte Esterase Test in Chlamydia trachomatis and Neisseria gonorrhoeae Infection Among Males Attending HIV/STI Clinics in Guangdong Province, China - Yu, Xueying; Zhao, Peizhen; Mai, Zhida; Xu, Qingqing; Chen, Wentao; Wu, Zhiqiao; Luo, Xiaojuan; Wu, Zhizhou; Liu, Xiaofeng; Wu, Qian; Zheng, Heping; Xue, Yaohua (Frontiers in Medicine, 2022)
Leukocyte esterase test (LET) detection is a simple and inexpensive test performed by urinalysis. This study investigated the predictive value of LET for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infection among men attending HIV and sexually transmitted infection (HIV/STI) clinics in Guangdong Province China. A total of 5,509 urine samples were collected from HIV and sexually transmitted infection clinics in Guangdong Province between 2017 and 2019. Specimens from 5,464 males were tested by both LET and nucleic acid amplification test (NAAT). Of 5,464 males, 497 (9.1%) tested positive for CT or NG by NAAT, with respective prevalence rates of 6.4% (95% confidence interval [95% CI]: 5.8%–7.1%) and 3.8% (95% CI: 3.3%–4.3%), including 1.2% (95% CI: 0.9%–1.4%) co-infected. Compared to the HIV-negative individuals, individuals living with HIV tend to have a higher prevalence of CT, NG and co-infection with CT and NG. The LET sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for CT were 46.4% (95% CI: 41.2%–51.7%), 92.0% (95% CI: 91.2%–92.7%), 28.4% (95% CI: 24.8%–32.1%), and 96.1% (95% CI: 95.6%–96.7%), respectively. The LET sensitivity, specificity, PPV, and NPV for NG were 68.4% (95% CI: 62.1%–74.7%), 91.8% (95% CI: 91.1%–92.6%), 25.0% (95% CI: 21.4%–28.5%), and 98.7% (95% CI: 98.3%–99%), respectively. Compared to the HIV-negative individuals, higher sensitivity and specificity were observed for HIV-positive individuals, but there was no statistical difference. The cost for identifying a CT-positive or NG-positive patient by NAAT was approximately $176.30 and $296.00, respectively. For LET-positive patients, the costs per positive CT or NG patient were approximately $82.20 and $93.80. LET is a cost-effective test and will be valuable for predicting CT and NG infection, which is highly prevalent in low- and middle-income countries.